2008
DOI: 10.1103/physrevlett.100.047208
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Liquid State of Hard-Core Bosons on the Pyrochlore Lattice

Abstract: We study the physics of hard-core bosons with unfrustrated hopping (t) and nearest-neighbor repulsion (V) on the three dimensional pyrochlore lattice. At half-filling, we demonstrate that the small V/t superfluid state eventually becomes unstable at large enough V/t to an unusual insulating state which displays no broken lattice translation symmetry. Equal time and static density correlators in this insulator are well described by a mapping to electric field correlators in the Coulomb phase of a U(1) lattice g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
231
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(239 citation statements)
references
References 30 publications
7
231
1
Order By: Relevance
“…The effects of certain types of quantum fluctuations on the spin ice state have been investigated theoretically 12 and numerically 13,14 , where they have been demonstrated to lift the classical degeneracy and promote a three-dimensional (3D) QSL phase with low-energy gapless excitations that behave like photons 12,13 [15][16][17] . In an attempt to elucidate the microscopic underpinnings of these and related materials, recent theoretical studies have produced a general low-energy effective spin-1/2 model for magnetism in rare earth pyrochlores [18][19][20] .…”
mentioning
confidence: 99%
“…The effects of certain types of quantum fluctuations on the spin ice state have been investigated theoretically 12 and numerically 13,14 , where they have been demonstrated to lift the classical degeneracy and promote a three-dimensional (3D) QSL phase with low-energy gapless excitations that behave like photons 12,13 [15][16][17] . In an attempt to elucidate the microscopic underpinnings of these and related materials, recent theoretical studies have produced a general low-energy effective spin-1/2 model for magnetism in rare earth pyrochlores [18][19][20] .…”
mentioning
confidence: 99%
“…In the low T limit, GB0.17 meV is similar to the spin flip energy 2J ff ¼ D w B1.6 K inferred from AC-w(T). The observation of a broad spectrum rather than a sharp spin flip mode indicates monopole quantum dynamics 12,14,15 . A possible low-energy regime of photons predicted for a U(1) spin liquid 12,14,15 , however, cannot be resolved in the present neutron scattering experiment.…”
mentioning
confidence: 99%
“…The classical nature of Ising spins precludes attainment of thermal equilibrium at temperatures (T) below the effective nearest neighbor energy scale J ff . Quantum fluctuations enhance dynamics and might allow coherent propagation of magnetic charge 12,13,14,15 , much as spinons in one-dimensional quantum magnets 16 .…”
mentioning
confidence: 99%
“…Recent numerical studies have found evidence that QED-like phenomena may be at play in some minimal quantum spin ice (QSI) lattice models [13] -but does the QSI picture apply to real materials? Also, should a QSI state be solely defined by whether or not a QSL state is realized?…”
mentioning
confidence: 99%